Devising a methodological approach to prioritizing road sections for maintenance work - Kharchenko, Anna; Tsybulskyi, Vitalii; Sokolova, Natalia; Shpyh, Alona; Kanin, Alexander; Smirnov, Oleh; Smirnov, Anatolii (Eastern-European Journal of Enterprise Technologies, 2025)
This study examines the process that prioritizes road sections for performing operational maintenance work to ensure compliance with the predefined level of requirements. The task addressed is to prioritize road sections in order to enable long-term network maintenance. This issue is due to objective circumstances related to the existing lack of long-term financing, poor filling of databases on the condition of roads, the need to take into account various criteria depending on the purposes of budget allocations. Unlike similar studies, in which the basis is a simple arrangement of objects by their priority, a methodological approach has been devised that is long-term-focused and includes further optimization of the road maintenance program. Importantly, an analytical hierarchical process (AHP) method was integrated into the mathematical model whose solution has been implemented in authentic RoadRange program. In practice, it allows road organizations to determine an effective, economically justified long-term program for operational maintenance of roads under an automated mode without additional costs for expensive software. The devised methodological approach to prioritizing sections of highways was tested using data from the Kyiv oblast (Ukraine). Based on the calculation results, 14 sections had been identified that were included in the potential long-term program and met relevant conditions and criteria. The effectiveness of program formation was proven by calculating the ratio of the consistency index to the repair index that equaled 0.002, which does not exceed the limit value of 0.10. The prospect of this study is to test the devised methodological approach at other critical infrastructure facilities and adapt it accordingly.